Analysis of Local Soil Stability Using Cement Added Additives (DIFA Soil Stabilize) in Tanjungpinang City Province Riau Island - Rahmadani, Niko; Puri, Anas; Syahminan, Mohammad (Jurnal Ilmu Dan Rekayasa Sipil, 2024)
Tanjungpinang City, located in Riau Islands Province, is predominantly characterised by Bauxite, Coral, and Sandy Loam soils, with a CBR value ranging between 8% and 10%. However, road pavement construction often encounters challenges due to the high Plasticity Index of the soil, making it difficult to achieve the minimum compaction standard. This study aims to evaluate the soil compaction and unconfined compressive strength (UCS) values through soil stabilisation using cement and the additive DIFA Soil Stabilizer, as well as to estimate the stabilisation cost. A quantitative method was employed, involving laboratory testing of the native soil mixed with cement (8%, 10%, 12%, 14% of the soil’s dry weight) and DIFA additive (1 kg/m³ of dry soil). The tests included the Standard Proctor Test and UCS test. Results indicated an increase in soil density: native soil achieved 1,323 kg/m³, while mixtures with 8% cement reached 1,460 kg/m³, 10% 1,470 kg/m³, 12% 1,470 kg/m³, and 14% 1,500 kg/m³. Soaked UCS values were as follows: 214.32 kN/m² (8%), 527.57 kN/m² (10%), 989.19 kN/m² (12%), and 1,005.68 kN/m² (14%). Unsoaked UCS values were: native soil 138.64 kN/m², 735.27 kN/m² (8%), 942.23 kN/m² (10%), 1,023.93 kN/m² (12%), and 1,813.51 kN/m² (14%). Stabilisation using cement and DIFA Soil Stabilizer effectively improved the soil's density and UCS values, making it a viable method for enhancing soil stability in Tanjungpinang.